Extracting Innovation Value from Intellectual Property: Evidence from sub-Saharan Africa - Joseph Amankwah-Amoah; Stephen Kehinde Medase (Journal of the Knowledge Economy, 2023)
Although a sizable body of research concerning innovation and intellectual property (IP) performance exists, there has been limited attention on whether the state of IP strengthens or curtails innovation activity in the global south, specifically among sub-Saharan Africa firms. This article analyzes the direct impacts of IP on innovation performance in sub-Saharan Africa, namely patents, copyrights, industrial designs, and trademarks. The paper responds to firms extracting value from intellectual property strategies through innovation activities and overall performance. Using the World Bank Enterprise Survey (WBES) and Innovation Follow-up Survey (IFS), we find that appropriation channels are essential for transforming innovation pursuits into a competitive advantage. Our results further reinforce that appropriation mechanisms are crucial to innovation and may allow firms to gain returns on their innovation activities. Regardless of the weaknesses and limitations of the patenting strategy in sub-Saharan Africa, the probability of patenting an innovation relates to a process and product innovation while controlling for several other effects. More importantly, we demonstrate how industrial designs and improved or changed trademarks can foster inclusive performance. In addition, we show that beyond perception-based innovations, intellectual property strategies also matter to innovation intensity and sales growth. Consequently, our results indicate that the significance of innovation for competitiveness puts intellectual capital at the critical juncture of knowledge management.
Keywords: O31; O34; O55; 330; Copyrights; Industrial designs; Patents; Trademarks; Multivariate Probit